The Importance of Multimodality Imaging in the Diagnosis and Management of Patients with Infiltrative Cardiomyopathies: An Update - Radu Sascău; Larisa Anghel; Alexandra Clement; Mădălina Bostan; Rodica Radu; Cristian Stătescu (Diagnostics, 2021)
Infiltrative cardiomyopathies (ICMs) comprise a broad spectrum of inherited and acquired conditions (mainly amyloidosis, sarcoidosis, and hemochromatosis), where the progressive buildup of abnormal substances within the myocardium results in left ventricular hypertrophy and manifests as restrictive physiology. Noninvasive multimodality imaging has gradually eliminated endomyocardial biopsy from the diagnostic workup of infiltrative cardiac deposition diseases. However, even with modern imaging techniques’ widespread availability, these pathologies persist in being largely under- or misdiagnosed. Considering the advent of novel, revolutionary pharmacotherapies for cardiac amyloidosis, the archetypal example of ICM, a standardized diagnostic approach is warranted. Therefore, this review aims to emphasize the importance of contemporary cardiac imaging in identifying specific ICM and improving outcomes via the prompt initiation of a targeted treatment.